Food Discourse in the Abbasid Era: A Study Selected from Poetry - أحمد صفاء علي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The Abbasid era witnessed a unique cultural and intellectual development, one of its most prominent features being the diversity and diversity of discourses. Among these discourses, the "discourse of food" stands out as a profound representation of intertwined cultural, social, and intellectual dimensions. Food in poetry is not merely a sensory term or a biological need; rather, it is a metaphor and symbol, a cultural manifestation, and a window into the interpretation of taste, power, identity, and beauty. Hence, an analysis of the discourse of food in Abbasid poetry reveals complex semantic layers that transcend the function of taste to reach multiple symbolic, aesthetic, and intellectual levels. The choice of poetry as a field for analyzing this discourse stems from its broader manifestation in this era. Poets expressed their worlds through the language of food: description, appetization, sarcasm, praise, satire, and sometimes as a tool of resistance or a symbol of authority. In this context, the dining table becomes a space for boasting or mockery, for revealing class disparities or manifestations of luxury, or even for intensifying the image of the poetic self through food metaphors.